Production, Properties And Applications Of Mycelium-Bound Lipase Of A Locally Isolated Strain Of Aspergillus Flavus Link - Long, Kamariah (1997)

(untitled)
One of the most promising processes using lipase which will offer great potential application especially in term of cost reduction, is the use of mycelium-bound lipase (naturally immobilized lipase). However, there has been little work reported on the technology using mycelium-bound lipase (naturally immobilize) and work using it, is limited to a few microorganisms. This study was conducted with the aims to identifying a new source of mycelium-bound lipase, and consequently to study it's production, properties and applications.Aspergillus flavus, isolated from copra meal, produces a lipase (EC 3.1.1.3) which is partly bound to the mycelium. The production of the mycelium-bound lipase is concomitant with growth, and declines when growth ceases. Maximum productivity of the enzyme is obtained when the culture is incubated at 30°C, an initial culture pH of 6.5 and with 2% (w/v) each of com oil and yeast extract as carbon and organic nitrogen sources, respectively. Yeast extract affects not only the production of lipase but also the secretion of proteases into the culture medium. The presence of EDTA improved the productivity of the mycelium-bound lipase by 26% although growth of A. flavus was inhibited by 11%. The addition of Tween 80, into culture medium, decreased the activity of mycelium-bound lipase.